Influence of root dentin treatment on the push-out bond strength of fiber posts - Baena, E.; Flores, A.; Ceballos, L. (2023)
The aim of the present study was to assess whether different dentin conditioning protocols with different acids [phosphoric acid, ethylene diamine tetra acetic acid (EDTA), and polyacrylic acid (PAA)] influence the bond strength of fiber posts along the radicular depth when luted with self-adhesive resin cement. Twenty single-rooted teeth were randomly divided into four experimental groups (n = 5) according to dentin treatment: Group 1: no treatment; Group 2: etching with 35 % phosphoric acid for 10 s; Group 3: 17 % EDTA application for 60 s; and Group 4: conditioning with 25 % PAA for 30 s. RelyX Fiber Posts were luted with the self-adhesive resin cement RelyX Unicem 2 Automix (3M ESPE). Roots were transversally sectioned into nine 1-mm thick specimens, three corresponding to each root third and a push-out test was performed. Data were analyzed by two-way ANOVA and Tukey test (p < 0.05). Failure mode was determined and specimens with representative failures for each group were observed under scanning electron microscopy. According to the results, dentin treatment influenced the bond strength (p < 0.001), whereas the root third did not (p > 0.05). Fiber posts luted after treating dentin with phosphoric acid, and PAA exhibited the highest push-out bond strength values, while the lowest were obtained after EDTA application. Intermediate results were obtained when dentin was not conditioned. In conclusion, the bond strength of the self-adhesive resin cement RelyX Unicem 2 improves when root dentin is treated with 35 % phosphoric acid or 25 % PAA, before fiber posts luting irrespective of the root depth.
Keywords: Tratamiento de Dentina; Poste de Fibra; Expulsar; Cemento de Resina Autoadhesivo; Capa de Frotis